2018
DOI: 10.1186/s12885-018-4631-z
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of hsa-miR-221, hsa-miR-21, hsa-miR-135b, and hsa-miR-29c suggests a field effect in oral cancer

Abstract: BackgroundThe theory of field effect suggests that the tumor-adjacent area, besides histopathologically normal, undergoes genetic and epigenetic changes that can eventually affect epithelial homeostasis, predisposing the patient to cancer development. One of the many molecular changes described in cancer are microRNAs (miRNAs), which regulates the expression of important genes during carcinogenesis. Thus, the aim of this study was to investigate the field effect in oral cancer.MethodsWe investigated the differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 68 publications
4
22
0
Order By: Relevance
“…[19][20][21][47][48][49][50][51][52][53] In cell culture studies, overexpression of hsa-mir-21-5p is associated with increased proliferation, migration, invasion, and colony formation as well as an decreased rate of apoptosis by targeting clusterin or PTEN. Numerous studies demonstrated an overexpression of hsa-mir-21-5p in OSCC/HNSCC tissue, blood samples, oral cytology samples, and cell lines.…”
Section: Hsa-mir-21-5pmentioning
confidence: 99%
See 1 more Smart Citation
“…[19][20][21][47][48][49][50][51][52][53] In cell culture studies, overexpression of hsa-mir-21-5p is associated with increased proliferation, migration, invasion, and colony formation as well as an decreased rate of apoptosis by targeting clusterin or PTEN. Numerous studies demonstrated an overexpression of hsa-mir-21-5p in OSCC/HNSCC tissue, blood samples, oral cytology samples, and cell lines.…”
Section: Hsa-mir-21-5pmentioning
confidence: 99%
“…Numerous studies demonstrated an overexpression of hsa-mir-21-5p in OSCC/HNSCC tissue, blood samples, oral cytology samples, and cell lines. [19][20][21][47][48][49][50][51][52][53] In cell culture studies, overexpression of hsa-mir-21-5p is associated with increased proliferation, migration, invasion, and colony formation as well as an decreased rate of apoptosis by targeting clusterin or PTEN. 17,18,22,23,51,54 Additionally, upregulated hsa-mir-21-5p has been shown to affect the well-known oncogenic WNT-β-catenin-pathway.…”
Section: Hsa-mir-21-5pmentioning
confidence: 99%
“…14 miR-221 has been suggested to be implicated in the development and progression of various cancers, such as ovarian cancer, hepatocellular carcinoma and oral cancer. [15][16][17] Moreover, miR-221 is suggested to be down-regulated and to serve as a potential biomarker for PD. 18 Additionally, miR-221 inhibits cell apoptosis and promotes neuronal survival in PD.…”
Section: Introductionmentioning
confidence: 99%
“…Transfection of the miR-7 precursor into AZ521 and Kato III GC cells signi cantly inhibited cell proliferation capacity (13). miR-135b has been described in the literature as an oncomiR in most tumor tissues, such as colon cancer (38), lung cancer (39), oral cancer (40) and breast cancer (41), but few studies have evaluated its role in gastric tissue. Vidal, Cruz (10) observed that miR-135b expression was increased in gastric lesions when compared with normal gastric mucosa but was decreased when gastritis tissue was compared with cancer tissue; thus, its role in the various stages of gastric carcinogenesis remains uncertain.…”
Section: Discussionmentioning
confidence: 99%